WASTEWATER TREATMENT BY USING BIOSYNTHESIZED NANOPARTICLES - FAIZ , A; ALI, MZ; NAWAZ, A; IQBAL, J; JAHANGIR, AN; DIN, HMU; QAMAR, F; KHAN, MJ; KHAN, AMA; SHEHERYAR, A (Biological and Clinical Sciences Research Journal, 2024)
Biosynthesized nanoparticles are a viable and sustainable approach for treating wastewater. They provide an environmentally acceptable alternative to traditional chemical synthesis processes. This review examines explicitly the production, use, and environmental consequences of nanoparticles created by biological methods, such as plant-mediated and microbial synthesis. The main aim of the review is to conduct a thorough assessment of the existing research on biosynthesized nanoparticles, focusing on identifying significant patterns, progress, and areas of knowledge lacking in the literature. The review consolidates results from current investigations, emphasizing the efficacy of these nanoparticles in eliminating organic pollutants, heavy metals, and other impurities from wastewater. The study also investigates the better characteristics of biosynthesized nanoparticles, including their reduced size, increased stability, and improved photoluminescence. These traits enhance their effectiveness in environmental cleanup. Nevertheless, the study highlights notable deficiencies in the existing body of research regarding the enduring ecological consequences and feasibility of implementing these environmentally friendly synthesis techniques on a large scale in industrial settings. The analysis continues by highlighting the necessity of consistent synthesis techniques and advocating for additional research on biosynthesized nanoparticles’ scalability and long-term impacts. These findings emphasize the capability of biosynthesized nanoparticles to improve wastewater treatment technologies and support sustainable environmental management. They also emphasize the significance of ongoing multidisciplinary research in this rapidly developing field.